PET/CT-Based Dosimetry in 90Y-Microsphere Selective Internal Radiation Therapy. Issue 23 (June 2015) - Song, Yoo Sung; Paeng, Jin Chul; Kim, Hyo-Cheol; Chung, Jin Wook; Cheon, Gi Jeong; Chung, June-Key; Lee, Dong Soo; Kang, Keon Wook; Zakko., Saad
<x xml:space="preserve">Abstract</x> Abstract 90Y PET/CT can be acquired after 90Y-microsphere selective radiation internal therapy (SIRT) to describe radioactivity distribution. We performed dosimetry using 90Y-microsphere PET/CT data to evaluate treatment efficacy and appropriateness of activity planning from 99mTc-MAA scan and SPECT/CT. Twenty-three patients with liver malignancy were included in the study. 99mTc-MAA was injected during planning angiography and whole body 99mTc-MAA scan and liver SPECT/CT were acquired. After SIRT using 90Y-resin microsphere, 90Y-microsphere PET/CT was acquired. A partition model (PM) using 4 compartments (tumor, intarget normal liver, out-target normal liver, and lung) was adopted, and absorbed dose to each compartment was calculated based on measurements from 99mTc-MAA SPECT/CT and 90Y-microsphere PET/CT, respectively, to be compared with each other. Progression-free survival (PFS) was evaluated in terms of tumor absorbed doses calculated by 99mTc-MAA SPECT/CT and 90Y-microsphere PET/CT results. Lung shunt fraction was overestimated on 99mTc-MAA scan compared with 90Y-microsphere PET/CT (0.060 ± 0.037 vs. 0.018 ± 0.026, P < 0.01). Tumor absorbed dose exhibited a close correlation between the results from 99mTc-MAA SPECT/CT and 90Y-microsphere PET/CT (r = 0.64, P < 0.01), although the result from 99mTc-MAA SPECT/CT was significantly lower than that from 90Y-microsphere PET/CT (135.4 ± 64.2 Gy vs. 185.0 ± 87.8 Gy, P < 0.01). Absorbed dose to in-target normal liver was overestimated on 99mTc-MAA SPECT/CT compared with PET/CT (62.6 ± 38.2 Gy vs. 45.2 ± 32.0 Gy, P = 0.02). Absorbed dose to out-target normal liver did not differ between 99mTc-MAA SPECT/CT and 90Y-microsphere PET/CT (P = 0.49). Patients with tumor absorbed dose >200 Gy on 90Y-microsphere PET/CT had longer PFS than those with tumor absorbed dose ⩽200 Gy (286 ± 56 days vs. 92 ± 20 days, P = 0.046). Tumor absorbed dose calculated by 99mTc-MAA SPECT/CT was not a significant predictor for PFS. Activity planning based on 99mTc-MAA scan and SPECT/CT can be effectively used as a conservative method. Post-SIRT dosimetry based on 90Y-microsphere PET/CT is an effective method to predict treatment efficacy.